Variant to Gene Mapping to Discover New Targets for Immune Tolerance - Mehra, Parul; Wells, Andrew D. (Frontiers in Immunology, 2021)
The breakdown of immunological tolerance leads to autoimmune disease, and the mechanisms that maintain self-tolerance, especially in humans, are not fully understood. Genome-wide association studies (GWAS) have identified hundreds of human genetic loci statistically linked to autoimmune disease risk, and epigenetic modifications of DNA and chromatin at these loci have been associated with autoimmune disease risk. Because the vast majority of these signals are located far from genes, identifying causal variants, and their functional consequences on the correct effector genes, has been challenging. These limitations have hampered the translation of GWAS findings into novel drug targets and clinical interventions, but recent advances in understanding the spatial organization of the genome in the nucleus have offered mechanistic insights into gene regulation and answers to questions left open by GWAS. Here we discuss the potential for ‘variant-to-gene mapping’ approaches that integrate GWAS with 3D functional genomic data to identify human genes involved in the maintenance of tolerance.